Antenatal magnetic resonance imaging versus ultrasound for predicting neonatal macrosomia: a systematic review and meta‐analysis. (29th July 2015) - Malin, GL; Bugg, GJ; Takwoingi, Y; Thornton, JG; Jones, NW
Abstract : Background: Fetal macrosomia is associated with an increased risk of adverse maternal and neonatal outcomes. Objectives: To compare the accuracy of antenatal two‐dimensional (2D) ultrasound, three‐dimensional (3D) ultrasound, and magnetic resonance imaging (MRI) in predicting fetal macrosomia at birth. Search strategy: Medline (1966–2013), Embase, the Cochrane Library and Web of Knowledge. Selection criteria: Cohort or diagnostic accuracy studies of women with a singleton pregnancy, who had third‐trimester imaging to predict macrosomia (>4000 g, >4500 g or >90th or >95th centile). Data collection and analysis: Two reviewers screened studies, performed data extraction and assessed methodological quality. The bivariate model was used to obtain summary sensitivities, specificities and likelihood ratios. Main results: Fifty‐eight studies (34 367 pregnant women) were included. Most were poorly reported. Only one study assessed 3D ultrasound volumetry. For predicting birthweight >4000 g or >90th centile, the summary sensitivity for 2D ultrasound (Hadlock) estimated fetal weight (EFW) >90th centile or >4000 g (29 studies) was 0.56 (95% CI 0.49–0.61), 2D ultrasound abdominal circumference (AC) >35 cm (four studies) was 0.80 (95% confidence interval [95% CI] 0.69–0.87) and MRI EFW (three studies) was 0.93 (95% CI 0.76–0.98). The summary specificities were 0.92 (95% CI 0.90–0.94), 0.86 (95% CI 0.74–0.93) and 0.95 (95% CI 0.92–0.97), respectively. Conclusion: There is insufficient evidence to conclude that MRI EFW is more sensitive than 2D ultrasound AC (which is more sensitive than 2D EFW); although it was more specific. Further primary research is required before recommending MRI EFW for use in clinical practice. Tweetable abstract: Systematic review of antenatal imaging to predict macrosomia. MRI EFW is more sensitive than ultrasound EFW. Tweetable abstract: Systematic review of antenatal imaging to predict macrosomia. MRI EFW is more sensitive than ultrasound EFW.